Analysis of Vladimir Propp's Narrative Functions in the Folktale Suri Ikun and the Two Birds: Analisis Fungsi Naratif Vladimir Propp dalam Cerita Rakyat Suri Ikun dan Dua Burung - Harahap, Annisah Inriani; Hasibuan, Safriyaldi Rahadi; Armis, Muhammad Khairi (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
Folklore plays a significant role in preserving cultural values and transmitting moral teachings across generations. This study aims to identify and describe the narrative functions proposed by Vladimir Propp in the folktale Suri Ikun and the Two Birds from Nusa Tenggara Timur, Indonesia. Employing a descriptive qualitative design with Propp's morphological approach, the study systematically analysed the textual data comprising sentences, paragraphs, and narrative events drawn from the folktale as published in the Indonesian Folklore Digital Collection (Kemdikbud, 2018). Data collection involved repeated close reading and note-taking, followed by inter-rater validation. Of the 33 narrative functions in Propp's canonical model, 22 were identified in the folktale: Initial Situation (α), Absentation (β), Interdiction (γ), Violation (δ), Trickery (η), Complicity (θ), Villainy (A), Lack (a), Beginning Counteraction (C), Departure (↑), First Function of the Donor (D), Hero's Reaction (E), Provision of a Magical Agent (F), Spatial Translocation (G), Victory (I), Liquidation of Lack (K), Return (↓), Pursuit (Pr), Rescue (Rs), Recognition (Q), Transfiguration (T), and Wedding (W). Eleven functions were absent, most notably Struggle (H) and Punishment (U), whose absence reflects the cultural tendency in Eastern Indonesian oral traditions to resolve conflict through moral endurance and supernatural reward rather than physical confrontation or retributive justice. These findings confirm that Propp's morphological framework is largely applicable across diverse cultural contexts, while also demonstrating that the selection and realisation of specific functions are culturally contingent.